2019
DOI: 10.1002/ccr3.2305
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of allergic bronchopulmonary mycosis: Experience of 55 patients with 124 relapses—A descriptive study

Abstract: There is no established consensus for the treatment of allergic bronchopulmonary mycosis (ABPM) on its diagnosis or at relapse. We reviewed our experience with patients with ABPM, which showed that although systemic corticosteroids are effective in ABPM, and other treatment options can also be selected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…There was in addition a significantly higher number of patients with steroid-related complications in the higher dose group. 76 A recent review by Ishiguro et al 77 into patients with ABPM showed that systemic corticosteroids are also effective in this related condition. Intravenous pulsed steroids have been studied and shown to be beneficial in children with refractory ABPA exacerbations associated with long-term steroid use.…”
Section: Current and Future Therapiesmentioning
confidence: 99%
“…There was in addition a significantly higher number of patients with steroid-related complications in the higher dose group. 76 A recent review by Ishiguro et al 77 into patients with ABPM showed that systemic corticosteroids are also effective in this related condition. Intravenous pulsed steroids have been studied and shown to be beneficial in children with refractory ABPA exacerbations associated with long-term steroid use.…”
Section: Current and Future Therapiesmentioning
confidence: 99%